2007
DOI: 10.1007/s10802-007-9190-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Response Timing in ADHD, Effects of Reinforcement Valence and Magnitude

Abstract: The present study investigated the impact of reinforcement valence and magnitude on response timing in children with ADHD. Children were required to estimate a 1-s interval, and both the median response time (response tendency) and the intrasubject-variability (response stability) were investigated. In addition, heart rate and skin conductance were measured to examine the autonomic responses to reinforcement. Feedback-only trials were compared to low response cost trials (response cost for incorrect responses)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…A number of researchers have argued that ADHD is a motivational problem, whereby individuals are unable to use intrinsic motivation to guide choice performance (Douglas, 1989; Sergeant et al, 1999). This is supported by evidence that children with ADHD perform well on continuous reinforcement schedules, whereas their performance deteriorates on partial reinforcement schedules where the consistent extrinsic motivation of reward is not provided (Parry and Douglas, 1983; Luman et al, 2008). …”
Section: The Breakdown Of Goal-directed Processes In Psychiatric and mentioning
confidence: 90%
“…A number of researchers have argued that ADHD is a motivational problem, whereby individuals are unable to use intrinsic motivation to guide choice performance (Douglas, 1989; Sergeant et al, 1999). This is supported by evidence that children with ADHD perform well on continuous reinforcement schedules, whereas their performance deteriorates on partial reinforcement schedules where the consistent extrinsic motivation of reward is not provided (Parry and Douglas, 1983; Luman et al, 2008). …”
Section: The Breakdown Of Goal-directed Processes In Psychiatric and mentioning
confidence: 90%
“…Some studies have found that ADHD-related increases in RTV are attenuated when rewards for performance are provided [12,14,[90][91][92], whereas others have not found this effect of reward [49,93]. Two studies in the literature have suggested that combining fast ER and reward can synergistically improve RTV [14,91].…”
Section: Reaction Time Variability Manipulationsmentioning
confidence: 99%
“…They appear to be less aware of the significance of feedback than controls, unless feedback is coupled with reinforcement (Luman, Oosterlaan, & Sergeant, 2008). Furthermore, they tend to prefer small immediate over larger delayed rewards (SonugaBarke, Sergeant, Nigg, & Willcutt, 2008), react with greater frustration to the loss of anticipated reward (Douglas & Parry, 1983, 1994 and exhibit a stronger tendency to seek reward (Scheres, Oosterlaan, & Sergeant, 2001).…”
mentioning
confidence: 99%